The Relationship Anxiety With Degree of Insomnia In The Elderly - Sincihu, Yudhiakuari; Daeng, B. Handoko; Yola, Priska (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
Anxiety is a mental disorder common in elderly people. In the process of becoming elderly, feelings of anxiety arise as a normal response to situations that accompany development, change, new experiences and find meaning in life. Anxious looks from physiological symptoms such as shaking, sweating, heart work increases and psychological symptoms such as panic, tension, confusion, unable to concentrate. This condition will inhibit the elderlys bio-psycho-social condition in living the rest of his life. One effect is seen from their sleep problems. This is observational research with cross-sectional approach. Samples were taken by consecutive sampling technique. 43 elderly who met the exclusion criteria. Research location at Posyandu Lansia Mojo, Surabaya. Data collection using Hamilton Rating Scale for Anxiety and Insomnia Severity Index questionnaires. the results of the study described 41.9% of subjects with anxiety disorders and 67.4% of subjects had insomnia disorders. The cross-tabulation results showed 48% of subjects without anxiety can occur insomnia disorders and only mild anxiety alone can cause insomnia in 100% of subjects. Rank Spearman Test shows a very strong relationship between anxiety with the incidence of insomnia in the elderly (Sig .000; coefficient correlation .535).